Inovasi Irigasi Tetes Otomatis Untuk Aquaponik Berbasis IoT - Risald, Risald; Baso, Budiman; Benu, Luky Wandika; Lestari, Anastasia Kadek Dety (Journal of Information and Technology, 2024)
Aquaponics is a sustainable food production system that combines fish farming (aquaculture) with growing plants without soil (hydroponics) in a symbiotic environment. One of the main challenges in an aquaponics system is ensuring efficient distribution of water and nutrients to the plants. This article discusses the development and implementation of an Internet of Things (IoT)-based automatic drip irrigation system designed to optimize water and nutrient distribution in aquaponic systems. This aquaponics control and monitoring system uses NodeMCU ESP8266, HC-SR04 Ultrasonic sensor, pH meter sensor, water pump, relay, RTC DS3231 module, and LCD + I2C module. The method for making this tool uses design and build engineering methods in making automation systems. The test results show that the system that has been created is able to work according to its respective uses and functions and provides feedback for farmers in increasing the productivity of agricultural products.